Parceria para Governo Aberto e Relações Internacionais: oportunidades e desafios - Guimarães, Caroline Burle dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation proposes an investigation to identify opportunities and challenges of Open Government Partnership (OGP) from the perspective of International Relations. By analyzing the concept of open government, it seeks to understand how it materializes in the case of OGP. To this end, it is studied the context of its creation in the current international conjunction, how important this juncture and the contribution of the study on open government for international relations, as well as the participation of Brazil since its incorporation, comparing it with Mexico – another pioneer in the creation of the Partnership. The research was based on the consideration that nation-states were forced to reorganize in light of the changes arising from globalization, interdependence and technological innovations in the media, with the positive speech on the establishment of a open government – which is based on democracy, the use of new technologies and citizen participation – began to attract governments and institutions. The governments that joined the OGP may have seen the possibility to show results in a more agile way, possibly with the help of nongovernmental organizations, by means of what he called citizen participation. The study also sought to ascertain to what extent the OGP can be seen as an initiative promoted by the U.S. government to explore the exercise of soft power. Regarding transparency and social control, OGP can serve to legitimize the governmental actions towards society. The hypotheses raised could be analyzed on the occasion of the analysis based on primary and secondary sources and discussions submitted by different authors, such as the documents made available by governments, academics, by policymakers and the original information provided by the interviewees in this research. Based on theories of Interdependence, Regimes and Governance, it was possible to comprehend the interaction of the concept of ...

Este trabalho propõe uma investigação para identificar oportunidades e desafios da Parceria para Governo Aberto (Open Government Partnership – OGP) sob a perspectiva das Relações Internacionais. Ao analisar o conceito do governo aberto, busca-se compreender como ele materializa-se no caso da OGP. Para tanto, estudou-se o contexto da sua criação na conjunção internacional vigente, qual a sua importância nessa conjuntura e qual a contribuição do estudo sobre governo aberto para as relações internacionais, assim como a participação do Brasil desde a sua constituição, comparando-a com a atuação mexicana – outro pioneiro na criação da Parceria. A pesquisa partiu da consideração de que os Estados nacionais foram obrigados a reorganizarem-se em função das mudanças advindas da globalização, da interdependência e das inovações tecnológicas nos meios de comunicação, com o que o discurso positivo sobre a instituição de um governo aberto – que tem como base a democracia, o uso de novas tecnologias e a participação cidadã – passou a atrair governos e instituições. Os governos que aderiram à OGP podem ter vislumbrado a possibilidade de mostrar resultados de maneira mais ágil, possivelmente com a ajuda de organizações não governamentais, por meio do que se chamou de participação cidadã. A pesquisa também procurou verificar em que medida a OGP pode ser vista como uma iniciativa promovida pelo governo dos Estados Unidos para explorar o exercício do soft power. No que diz respeito à transparência e ao controle social, a OGP pode servir para legitimar ações governamentais perante a sociedade. As hipóteses suscitadas puderam ser analisadas por ocasião das análises feitas com base nas fontes primárias, secundárias e nas discussões apresentadas pelos diferentes autores, como os documentos disponibilizados pelos governos, por acadêmicos, pelos formuladores de políticas públicas e pelas...
Keywords: Relações internacionais; Sociedade civil; Governança; Comunicação na política; International relations